KARAKTERISTIK WINE SALAK YANG DI PRODUKSI DI KABUPATEN KARANGASEM DAN KABUPATEN TABANAN - I Nyoman Wiratnaya; I Nyoman Rinala; I Wayan Adi Darmawan (JURNAL GASTRONOMI INDONESIA, 2019)
Indonesia as a Tropical Country has a diversity of fruits with high aesthetic values,recorded several fruits such as Pineapple, apple, orange, mango, jackfruit, papya,rambutan, zalacca, and others. From the diversity of fruits that are many in Indonesiaare zalacca (Salacca). Fruit salak is a native Indonesian fruit that is rememberedby the community, including Balinese salak which is a type of zalacca which isloved by the people because it tastes sweet, the fruit is thick and yellow, the seedsare small and have small scales on the fruit skin. Salak products in Bali Provincecontinue to increase as souvenirs but can be processed into wine products. SibetanVillage Karangasem Regency, Bali Province is famous for its salak Bali. Accordingto Suter (1988: 23) there are 10 local Balinese salak cultivars, among others, whitezalacca, granulated sugar, and salak bogor. Based on observations of fruit morphologyin the color of the physical arrangement of the shape and size of fruit, while salakhut, jackfruit zalacca, pineapple bark, copying bark, coconut bark, and salak boni arerather difficult to distinguish between salak one and the other salak. The most salakproduced in Karangasem Regency is Jackfruit snake with fruit characteristics thathave a round shape, medium size, blackish brown, milk-colored flesh, sweet flavorrather tight and there is a smell like jackfruit. Salak is mostly produced in Karangasem,precisely in Sebetan Village, the results obtained are abundant at the time of the salakharvest, which are sold at a low price rather than being stored for a long time anddecaying. preserving it like zalacca into wine. Wine is a type of processed salak whichhas a high selling price for other types of processed products. As well as coveringthe international market because of the taste of wine that is commonly accepted byconsumers throughout the World. In general, people know that wine is made from grapes but salak can be made into wine known as Fruit wine. Fruit wine is a fermentedalcoholic beverage and all types of wine. an example of fruit wine is salak wine.While in Cepaka Village in Tabanan Regency is a production of salak wine, whosebasic ingredients come from Sibetan, while the two ingredients are the same but theresults are different. Identifying the same problem with salak with different productionsites, the wine yield will be different. Problem Formulation: What is the wrong winecharacteristic produced in Karangasem Regency with salak wine produced in TabananRegency?Types and Data Source Qualitative Data and Quantitative Data: Primary andSecondary Data SourcesOrganulatic Test: Organulatic Test According to Hartle (2017:78) describes the basic steps in assessing having 2 bases, namely: 1. Sweetness, 2.Acidity (acidity), 3. Tannin (shoe), 4. Alcohol level (alcohol level), 5. Body (density),6. Flavor and Flavor intensity (sense of intensity of feeling), 7. The final fin (long andfinal). Whereas according to Robert Joseph and Margaret Rand (2000: 80) mentionthere are 6 basic characters in assessing wine, namely 1. Fruit, 2. Alcohol, 3. Acidity(acidity), 4. Sweetness (sweetness), 5. Tannin ( tight), 6. Body (density)